A critical study on the compliance of the Islamic banking system home financing in Malaysia to the syariah principles /Afiqah Amran...[et al.] - Amran, Afiqah; Sedik, Nurul Ain; Hamdan, Nurul Hidayah; Zainul Abidin, Siti Nur Hasanah (2011)
The area of study is on the Compliance of the Islamic Banking System Home Financing in Malaysia to the Syariah Principles.The aims of studies are to critically analyze about the Islamic Banking system in Malaysia focusing on home financing and secondly, to determine whether the product of home financing in Islamic Banking system in our country is in compliance with Syariah principles. These analyses of study emerge from different aspects including the proper understanding of concept Bai Bithaman Ajil and Musharakah Mutanaqisah in practice by the financier and the various tools in Syariah principles such as Murabahah, Bai- at Inah and Ijarah concept respectively. This paper finds that Bai Bithaman Ajil still has some loopholes in this product which not entirely accordance to the Syariah principle especially in the issue high selling price which lead to the oppression of the customer. Musharakah Mutanaqisah is a clear alternative to avoid interest and can reduce the cost of house financing and ultimately the duration of financing. Even though Musharakah Mutanaqisah has some weaknesses but it protects the benefits and public interests. In comparison, Musharakah Mutanaqisah is well accepted and implemented worldwide than Bai Bithaman Ajil As conclusion, Islamic banking and finance must ensure that all of its transactions are Syariah compliant not only on its legal technicalities and forms but more importantly the economic substance which is premised on the objectives outline by Syariah,